2012
DOI: 10.1146/annurev-earth-042711-105545
|View full text |Cite
|
Sign up to set email alerts
|

Extratropical Cooling, Interhemispheric Thermal Gradients, and Tropical Climate Change

Abstract: Recent studies suggest the existence of a global atmospheric teleconnection of extratropical cooling to the tropical rainfall climate, mediated through the development of a thermal contrast between the hemispheres-an interhemispheric thermal gradient. This teleconnection has been largely motivated by studies that show a global synchronization of rapid climate change during abrupt climate changes of the last glacial period, in addition to attribution studies of twentieth-century Sahel drought and studies that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
254
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(287 citation statements)
references
References 109 publications
32
254
1
Order By: Relevance
“…This tallies with previous studies that have shown that an increase in the albedo causes a change in the atmospheric energy transports, brought about by a change in the position of the zonal mean ITCZ (Chiang and Bitz 2005). Figure 4 shows that the heat transport across the equator is partitioned approximately equally between the atmosphere and the ocean.…”
Section: A Albsupporting
confidence: 88%
See 3 more Smart Citations
“…This tallies with previous studies that have shown that an increase in the albedo causes a change in the atmospheric energy transports, brought about by a change in the position of the zonal mean ITCZ (Chiang and Bitz 2005). Figure 4 shows that the heat transport across the equator is partitioned approximately equally between the atmosphere and the ocean.…”
Section: A Albsupporting
confidence: 88%
“…Although many studies report that with an increase in elevation the surface cools, it is unclear whether this cooling is due merely to lapse rate effects, to the fact that a higher surface will be cooler, or to additional feedbacks that alter the climate's energy balance, particularly those that reduce the amount of energy incident at the surface. Slab model experiments in which the topography and albedo are changed individually (Chiang et al 2003) show that there are feedbacks that can alter the response of the atmosphere to an ice sheet: they also emphasize the nonlinearity of these feedbacks highlighting the differences between an albedo-alone response and a topography-alone response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although with some uncertainties, we believe that the proposed ideas construct a coherent regional interpretation, explaining the 3 He and 36 Cl ages reasonably from Coropuna, Hualca Hualca and their surroundings ( [7,37]; this work), as well as the other glacial chronologies available from the Arid Tropical Andes: Sajama [121], Tunupa [8] and Uturuncu [9]. The glacial ages and paleoclimatic proxies seem consistent with evidence showing a link between tropical glaciers and the Northern Hemisphere cooling episodes, through the tropical circulation southward shift [20][21][22][23][24]. [37,38]; This work; Hualca Hualca [7], Sajama [121] Tunupa [8] and Uturuncu [9].…”
Section: The Last Glacial Maximum and Deglaciation In The Arid Tropicsupporting
confidence: 82%